Superhero Shakespeare in Golden Age Comics - Ciraulo, Darlena (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
Albert Lewis Kanter launched Classic Comics in 1941, a series of comic books that retold classic literature for a young audience. Five of Shakespeare’s celebrated plays appear in the collection. The popularity of Classics Illustrated encouraged Seaboard Publishing to issue a competitive brand, Stories by Famous Authors Illustrated (1949-51), which retold three Shakespearean dramas. Although both these enterprises aimed to reinforce a humanist perspective of education based on Western literature, the classic comics belie a Posthuman aesthetic by presenting Shakespearean characters in scenes and postures that recall Golden Age superheroes. By examining the Shakespearean covers of Classic Illustrated and Stories by Famous Authors, this essay explores how Shakespearean characters are reimagined as Superhuman in strength and power.